2015
DOI: 10.1007/s00253-015-7075-2
|View full text |Cite
|
Sign up to set email alerts
|

Entomotoxic and nematotoxic lectins and protease inhibitors from fungal fruiting bodies

Abstract: Fruiting bodies or sporocarps of dikaryotic (ascomycetous and basidiomycetous) fungi, commonly referred to as mushrooms, are often rich in entomotoxic and nematotoxic proteins that include lectins and protease inhibitors. These protein toxins are thought to act as effectors of an innate defense system of mushrooms against animal predators including fungivorous insects and nematodes. In this review, we summarize current knowledge about the structures, target molecules, and regulation of the biosynthesis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 180 publications
(272 reference statements)
2
59
0
Order By: Relevance
“…mites and insect larvae). Many of the observed characteristics for aegerolysin proteins in A. niger resemble those described for secondary metabolites and lectins in fungi who act as defence molecules in organisms that produce them (Calvo et al ., ; Mylonakis et al ., ; Künzler, ; Sabotič et al ., ). Therefore, this leads us to believe that the main role(s) of aegerolysins in A. niger are linked to the defence/protection of the fungus during the sensitive period of its development, rather than to growth and development of the fungus.…”
Section: Discussionmentioning
confidence: 97%
“…mites and insect larvae). Many of the observed characteristics for aegerolysin proteins in A. niger resemble those described for secondary metabolites and lectins in fungi who act as defence molecules in organisms that produce them (Calvo et al ., ; Mylonakis et al ., ; Künzler, ; Sabotič et al ., ). Therefore, this leads us to believe that the main role(s) of aegerolysins in A. niger are linked to the defence/protection of the fungus during the sensitive period of its development, rather than to growth and development of the fungus.…”
Section: Discussionmentioning
confidence: 97%
“…Although lectins from plants and other species have been an important topic of research for years, most studies dealt with the identification and expansion of a particular lectin family in one species, or specifically focused on one type of lectin motif and its distribution in the plant kingdom [27,28,29,30,31,32,33,34,35,36]. To date, there have only been a few publications that report on the distribution of multiple lectin motifs across plant species.…”
Section: Introductionmentioning
confidence: 99%
“…MpL differs from other fungal entomotoxic and nematotoxic β-galactoside-binding lectins, which were shown to have negative effects on the proliferation of mammalian cell lines [6]. Treatment of human cell lines showed that, even at fairly high concentrations, MpL has no effect on cell viability/proliferation, but is rapidly internalized and accumulated within certain subcellular compartments.…”
Section: Discussionmentioning
confidence: 98%
“…The first discovered and the most extensively investigated are lectins from plants, however, in recent years fungal lectins have been gaining more attention [4,5]. Fungal lectins differ from their counterparts from other species in their unique structures and binding specificities [6]. They have shown to be very stable proteins, resistant to changes in pH and temperature as well as to proteolytic digestion, which strengthens their potential for application in biotechnology and medicine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation